Efek Antihiperurikemia Ekstrak Air Kelopak Bunga Rosela (Hibiscus sabdariffa L.) pada Tikus Putih Wistar Jantan - Wahyuningsih, Sri; Yulinah, Ellin; Sukrasno, .; N, Karina (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2015)
Antihyperuricemia effectivity had been studying of water extract roselle calyx (Hibiscus sabdariffa L.) in Wistar male rats used at 46.25 mg/kgBW, 92.5 mg/kgBW and 185 mg/kgBW by using uricostatic methods. In uricostatic method had used drug comparison alopurinol 9 mg/kgBW of an induced with potassium oxonate 250 mg/kgBW peritoneally and high purin diet which contained 10% seed of Gnetum gnemon administrations within 14 days. The test of uric acid content had observed on day 1, 7 and 14. The results showed in uricostatic method with alopurinol as drug comparison that water extract of roselle calyx at doses 46,25 mg/kgBW and 185 mg/ kgBW had capability decreased the level of uric acid (p